1977
DOI: 10.1115/1.3448774
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Impact Between Curved Liquid Surface and Rigid Flat Surface

Abstract: The impact process of a cylindrical, a spherical and a conical water drop upon a rigid plane is studied with numerical methods. Time variation of drop cross-section, pressure and velocity distribution are presented. The maximum pressure remained at the center of the contact area for the cylindrical drop, but expanded outward with the edge of the contact area for the spherical and conical drops. The peak pressure for both cylindrical and conical drop reached approximately the value predicted by a one-dimensionl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…2. As the duration of this liquid-jet impact is very short [17,18], it can be considered as a point force. The incident laser energy is 34 mJ and the distance L from the laser focus to the boundary is 0.12 mm.…”
Section: Resultsmentioning
confidence: 99%
“…2. As the duration of this liquid-jet impact is very short [17,18], it can be considered as a point force. The incident laser energy is 34 mJ and the distance L from the laser focus to the boundary is 0.12 mm.…”
Section: Resultsmentioning
confidence: 99%
“…A quick look at these studies and similar ones in the literature reveals that, more often than not, a corrected version of the water hammer equation is used to estimate the impact pressure in liquid drop impact on solid target and less effort has been made to study the impact pressure behavior over time. The numerical study by Hwang and Hammit [58], for example, is one of the earliest works in which the transient impact pressure and its time evolution was investigated. For various liquid body geometries including spherical drops, in the case of a 300 m/s impact, they reported that the maximum pressure on the central axis of the drop is approximately 0.7 water hammer pressure and that the maximum pressure overall is experienced near the contact line and is almost equal to the water hammer pressure.…”
Section: Simulation Results and Validationmentioning
confidence: 99%
“…Several researchers used the N-S equations of viscous fluid (the fluid model) or Euler equations of non-viscous fluid to solve the flow and pressure field in the water drop during impact [23,24,29]. The N-S equations include at least 4 strong nonlinear equations, and the computation cost is very expensive when solving the dynamic pressure field in liquid.…”
Section: Previous Models In Liquid Regionmentioning
confidence: 99%
“…For example, refs. [23,24] analyzed the liquid-solid impact by using the Compressible-Cell-and-Marker method. Their approach did not predict the formation of shock wave and did not satisfy the water hammer force on the central axis [5].…”
Section: Previous Numerical Studies On Liquid-solid Impactmentioning
confidence: 99%